Design of 100 MW LNG Floating Barge Power Plant - I Made Ariana; Hari Prastowo; Aldio Paruna (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2017)
Floating barge power plant able to supply amount of electricity to undeveloped island in Indonesia. In this research, the generator will be use in the power plant is dual-fuel engine. The process was determine the engine and every equipment along with its configuration then arrange the equipment. The result, MAN18V51/60DF selected along with its system configuration and its general arrangement. The final design enable 7.06 days of operation with daily average load (64.76 MW) or 4.57 days with continues 100 MW load. In the end, the mobile power plant can be built on Damen B32SPo9832 Barge and comply with the regulation.